ABCD: Responding to Common In-Hospital Emergencies - Julianna Jung; Nicole Shilkofski (Association of American Medical Colleges, 2011)
Abstract Introduction This is a four-case simulation curriculum for second-year medical students preparing to begin their clinical rotations. The goal of the curriculum is to prepare students to cope with the first few minutes of in-hospital emergency situations until help arrives. Methods Learners rotated through the 60 minute scenarios in seven or eight person groups. Scenarios covered common in-hospital emergencies: respiratory arrest with need for assisted ventilation and noninvasive airway management, cardiac arrest with need for defibrillation, shock with need for IV access and volume administration, and altered mental status with need for assessment and glucose administration. At each scenario, the preceptor provided a brief introduction to the case, after which the learners will complete the scenario "cold." The preceptor then debriefed the group, emphasizing strengths and providing specific feedback on weaknesses. The group then completed the scenario again followed by a short wrap-up debriefing before rotating to the next station. Results We measured the effect of the curriculum using a control group that consisted of 24 third- and fourth-year students and a study group that consisted of 26 second-year students. Compared to the control group, students in the study group were more likely to perform several key resuscitation maneuvers in a timely fashion. The study group was also more likely to administer oxygen, request IV access, and perform rapid defibrillation, though these results were not significant. Discussion Overall, we believe that with instruction and practice, early medical students can master the basic skills required to assess and initiate management for an acutely ill patient during the brief period before help arrives. This will allow them to enhance the safety of their patients, improve their confidence as budding clinicians, and give them a foundation on which to build future resuscitation skills.